The Effect of Antibiotics on the Nervous System: Importance for Anesthesiology and Intensive Care - Paweł Radkowski; Julia Oszytko; Kamil Sobolewski; Florian Trachte; Dariusz Onichimowski; Marta Majewska (Antibiotics, 2025)
Background: Due to the high prevalence of severe infections, antibiotics are frequently administered in anaesthesia and intensive care units. Despite their therapeutic efficacy, several antibiotics exhibit neurotoxic potential, resulting in central and peripheral neurological complications in patients. This review aims to summarise the current evidence on antibiotic-induced neurotoxicity, particularly in critical care settings. Methods: A comprehensive literature analysis was performed to assess the neurotoxic profiles, underlying mechanisms, and clinical manifestations associated with different antibiotic classes, including beta-lactams, fluoroquinolones, macrolides, aminoglycosides, and others. Results: Beta-lactam antibiotics (especially cephalosporins and carbapenems) are strongly associated with seizures, encephalopathy, and EEG abnormalities, mainly through GABAergic inhibition and mitochondrial dysfunction. Fluoroquinolones and macrolides can cause psychosis, insomnia, and neuropathy via NMDA activation and oxidative stress. Linezolid carries the risk of serotonin syndrome and optic neuropathy, while glycopeptides and aminoglycosides are primarily associated with ototoxicity. Risk factors include advanced age, renal or hepatic impairment, and high serum drug levels. Conclusions: The neurotoxic potential of antibiotics is a critical but under-recognised aspect of pharmacotherapy in intensive care. Improved awareness, pharmacovigilance, dose adjustment, and drug monitoring are crucial for mitigating adverse neurological effects.